The shift in students’ perspectives on physical activity: the contrasting nature of individual preferences - Glazkova G.B.; Mamonova O.V.; Dubrov A.A.; Lubyshev E.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to identifying individual and collective preferences for physical activity among students. Methods and structure of the study. Based on the findings of the Plekhanov Russian University of Economics, a study was conducted among students (n=1272) to explore their physical activity patterns during the academic day. The results were compared with the findings of previous research conducted in 2020-2022. Results and conclusions. The students are divided into two categories: those who do not engage in physical activity and those who express a desire to lead a healthy lifestyle and participate in physical activity two to three times a week. The use of exercises for general physical development has decreased, with a shift in focus towards preventing posture disorders, developing strength, and improving coordination. Among the students in the second group, we observed a shift in priorities towards a healthy lifestyle, with a strong emphasis on family, school, and university values. The cohort prioritizes physical activity in the comfortable environment of «digital self-isolation». The academic discipline «Physical Culture» is essential for all students, serving as a foundation for the development of a secondary need for physical activity for the first group and a competent approach to exercise selection for the second group.